Alternative to Chemotherapy—The Unmet Demand against Leishmaniasis - Didwania, Nicky; Shadab, Md.; Sabur, Abdus; Ali, Nahid (Frontiers in Immunology, 2017)
Leishmaniasis is a neglected protozoan disease that mainly affects the tropical as well as subtropical countries of the world. The primary option to control the disease still relies on chemotherapy. However, a hindrance to treatments owing to the emergence of drug-resistant parasites, enormous side-effects of the drugs, their high cost, and requirement of long course hospitalization has added to the existing problems of leishmaniasis containment program. The current review highlights the prospects of immunotherapy and/or immunochemotharapy to address the limitations for current treatment measures for leishmaniasis. In addition to the progress in alternate therapeutic strategies, the possibility and advances in developing preventive measures against the disease has been pointed. The review highlights our recent understandings of the protective immunology that can be exploited to develop an effective vaccine against leishmaniasis. Moreover, an update on the approaches that have evolved over the recent years are predominantly focused to overcome the current challenges in developing immunotherapeutic as well as prophylactic anti-leishmanial vaccines is discussed.